Stratégies musicales de préservation et d'adaptation chez les Urainiens-Montréalais - Berthiaume-Zavada, Claudette (MUSICultures, 1989)

Judeo-Spanish Song in the Sephardic Communities of Montreal and Toronto - Cohen, Judith R. (Université de Montréal, 1989)

"Ya salio de la mar": Judeo-Spanish Wedding Songs among Moroccan Jews in Canada - Cohen, Judith R. (Women and Music in Cross-Cultural Perspective, 1989)

Who's Who of Jazz in Montreal: Ragtime to 1970 - Gilmore, John (Véhicule Press, 1989)

La pratique de la musique liturgique et paraliturgique des Juifs originaires du Maroc à Montréal - Sabbah, Dina (Université de Montréal, 1989)

Petite histoire des musiques afro-montréalaises - Villefranche, Robert; Bernard, Yves (MUSICultures, 1989)
Robert Villefranche and Yves Bernard describe the history of Montreal musicians of African descent, telling of the formation of various groups that performed at community events and festivals and became more widely known through recordings and festivals.